REMOTE CONTROLLING OF AN AGRICULTURAL PUMP SYSTEM BASED ON THE DUAL TONE MULTI-FREQUENCY (DTMF) TECHNIQUE - BEZA N. GETU; NASSER A. HAMAD; HUSSAIN A. ATTIA (Journal of Engineering Science and Technology, 2015)
In modern days, as a result of advances in technology, human beings are interested to remotely control different systems and applications. In this work, telephone signalling technique using Dual Tone Multi-Frequency (DTMF) signalling, is used to control switching of electrical loads such as agricultural pumps located in remote areas. A DTMF tone command sent from a transmitting fixed or mobile phone terminal will be used to SWITCH ON/OFF the motors used to pump water for agricultural fields. A processing electronic system at the receiving side is designed to interpret the tone commands and sends an appropriate signal to the motor driving circuit to complete the pump switching states. In the design methodology, it is possible to control several water pumps distributed in a certain agricultural site, however, in this work we considered four pumps and the paper presents the complete electronic design and simulation results at the different stages of the design. The electronic design is based on discrete passive and active electronic components and the system is tested and simulated using Multism program. The results of the simulation show that the design is capable of controlling the switching state of the motors. For a certain DTMF command, it is possible to switch ON/OFF a specific motor pump or all of the four motors.